Wealth, Law, and Moral Authority: Marriage and Christian Mobilization in Interwar Cameroon - Walker-Said, Charlotte (The International journal of African historical studies, 2015)
Before European colonization, bridewealth was a form of matrimonial compensation paid principally in bikié, or iron bars, along with kola nuts, palm wine, tools, and livestock, which then incorporated guns and ivory in the early and mid-nineteenth century and German marks after 1885.10 During the interwar years, a rapidly expanding economy with complex systems of African labor management-overseen by French concessionary societies as well as administration-appointed African chiefs-generated new demands as part of bridewealth, including hard currency, as well as livestock, alcohol, tobacco, and luxury or prestige goods like metals and imported liquors.11 In Cameroon's major cities, wealthy families expanded their demands to include fine clothes, bicycles, automobiles, and sometimes tens of thousands of francs in cash.12 This inflation provoked outrage among foreigners as well as locals, prompting the administration to pass a series of laws against "bride commerce" and missionaries to restrict sanctified marriages to those who eschewed bridewealth exchange entirely.13 Burgeoning African Catholic congregations and communities also countered bridewealth aggrandizement by creating outlets for unmarried youth and young couples to critique the practice.